Unilateral Grave's Disease: A case report - Gözel, Nevzat; Kılınç, Faruk; Demircan, Fatih (Fırat University, 2014)
Graves' disease is a a rare autoimmune thyroid disease that characterized by hyperthyroidism, diffuse goiter, infiltrative ophthalmopathy, infiltrative dermopathy and thyroid akropachy. It usually affects both lobes of the thyroid, unilateral involvement have been reported rarely. In our clinic we diagnosed unilateral graves disease wich has single-sided involvement (in other thyroid lobe and isthmus agenesis-hemiagenesis) in cintigraphy. Thus we presented a rare unilateral graves case with current literature.

Graves hastalığı; hipertiroidi, diffüz guatr, infiltratif oftalmopati, daha nadir olarak infiltratif dermatopati ve tiroid akropatisi ile karekterize otoimmün bir tiroid hastalığıdır. Genellikle her iki tiroid lobunu da etkilemesine rağmen, tek taraflı tutulum nadir olarak bildirilmiştir. Kliniğimizde tanı konulan, sintigrafide tek taraflı tutulum gösteren (diğer lob ve isthmus agenezik-tiroid hemiagenezisi) nadir görülen bir olgu olan unilateral graves hastalığı güncel literatür eşliğinde sunulmuştur.
Unilateral Grave's Hastalığı: Olgu sunumu